THE APPLICATION OF MUSICAL INTELLIGENCE-BASED MATHEMATICS LEARNING ON PLANE SHAPE DISCUSSION - Ismah, Ismah; Prasetyo, Bayu Aji Eko (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
In this study, Gardner's theory of multiple intelligences was used to conduct experimental research on several elementary school students at TPQ Al-Ikhwan Meruya Jakarta, Indonesia. The initial stage of this study was to classify the types of student intelligence using multiple intelligence instruments adopted from Shearer in 1997. Furthermore, learning strategies are applied to students according to the kind of intelligence. This study observed the differences in mathematics learning outcomes of students who have musical intelligence before and after the application of interactive learning media in the form of music containing a song with the title "Aku Bangun Datar" and the lyrics are examples of a two-dimensional figure with natural objects. The research method used was a quantitative quasi-experimental type with a pre-test-post-test design. Research data analysis using a statistical t-test for the difference in the mean of the two populations. The results of data analysis obtained a t value of -8,000, while the t table is -2.0686. The comparison between the t value and the t table is known that t is more significant than the t table, so the hypothesis is rejected. It means that there is a significant difference in students' knowledge about shapes before and after using music media.